Perspectivas de la población local sobre condiciones y transformaciones socio-ambientales en el Cantón Macará (Provincia de Loja, Ecuador). Caso de estudio Sabiango - Kieslinger, Julia; Hualpa Erazo, Angel; Rengel Vega, Paola (2021)
As part of the doctoral thesis "The Importance of Spatial (Im)mobilities in the Context of Changing Life Conditions and Lifeworlds: The Example of Socio-Ecological Transformation in Rural Ecuador" (forthcoming), this report addresses the grassroots views of the participants in this research and gives them an arena to express their concerns about local living conditions and challenges. In a few sections, additional information from secondary data was included when it was considered of added value to the reader to embed the local participants’ views in a broader context. In order to implement the principles of the participatory research design, this report is dedicated to the local government administrations of the Parroquia Sabiango and the Cantón Macará (Ecuador) who can communicate and disseminate these findings among different actors in the field.<br